2022
DOI: 10.3389/fphys.2022.1025839
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of combined isometric and plyometric conditioning activities on sports performance and tendon stiffness in female volleyball players

Abstract: This study aimed to compare the effects of bilateral and unilateral conditioning activities (CA; combined isometric and plyometric) on countermovement jump performance, modified t-agility test, Achilles tendon stiffness and skin surface temperature. Thirteen female semi-professional volleyball players performed two CAs in random order: 1) bilateral isometric half back squats followed by bilateral drop jumps (BI-CA); and 2) unilateral isometric half back squats followed by unilateral drop jumps (UNI-CA). To ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several authors have shown JH enhancement after voluntary isometric effort 19 , 34 , 44 , with Kalinowski et al 44 showing enhanced JH and Spieszny et al 19 demonstrating jump improvement among handball payers. Interestingly, peak performance showed wide variability, with some individuals peaking after four minutes and others peaking after eight.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown JH enhancement after voluntary isometric effort 19 , 34 , 44 , with Kalinowski et al 44 showing enhanced JH and Spieszny et al 19 demonstrating jump improvement among handball payers. Interestingly, peak performance showed wide variability, with some individuals peaking after four minutes and others peaking after eight.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most crucial factors for effective PAPE is appropriate intensity. Indeed, an effort of approximately 80%-RM is submaximal ( Seitz and Haff, 2016 ; Dobbs et al, 2019 ), though positive effects are observed with higher and lower loads ( Gołaś et al, 2017 ; Vargas-Molina et al, 2021 ) or by using voluntary contractions ( Kalinowski et al, 2022 ; Spieszny et al, 2022 ). In this regard, the intensity of the CA and rest intervals are also crucial ( Dobbs et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their data are similar to the current study findings in relation to time to performance enhancement and intensity used. On the other hand, isometry can be combined with plyometric other activities, what increased jump performance effectively in female volleyball players ( 20 ). However, in contrast to the current study and that of Vargas-Molina et al ( 39 ), there was no relative external load, and subjects had to push on an immovable bar.…”
Section: Discussionmentioning
confidence: 99%